The Relationship between Emotional Intelligence and Psychological Well-being in Early Childhood - Nasywa Dhiya Amatulloh Sholihah; Idat Muqodas (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study examines the relationship between emotional intelligence and psychological well-being in early childhood. Data were collected using a quantitative correlational design from 57 parents of kindergarten children in Purwakarta selected through purposive sampling. Emotional intelligence was measured with the Parental Emotional Intelligence Scale (23 items: self‑awareness, self‑regulation, motivation, empathy, social skills), and psychological well‑being with the Early Childhood Psychological Well‑Being Questionnaire (18 items: positive affect, life satisfaction, absence of distress). Instrument validity was confirmed through item–total correlation, and reliability analysis produced a Cronbach’s alpha of 0.935. Normality and linearity tests showed that the data met the assumptions for Pearson product–moment correlation. The results indicated a strong, positive, and statistically significant relationship between emotional intelligence and psychological well‑being (r = 0.647, p < 0.001). This finding adds empirical evidence on the emotional intelligence–well‑being link in an understudied Indonesian early childhood context and highlights the crucial role of parental emotional intelligence. The study recommends integrating parent‑focused emotional intelligence learning into early childhood education programs to promote children’s psychological well‑being.